2020
DOI: 10.1017/s0305000920000240
|View full text |Cite
|
Sign up to set email alerts
|

Use of a head camera to examine maternal input and its relation to 10- to 26-month-olds’ acquisition of mental and non-mental state vocabulary

Abstract: We examined the relation between maternal responsiveness and children's acquisition of mental and non-mental state vocabulary in 59 pairs of mothers and children aged 10 to 26 months as they engaged in a free-play episode. Children wore a head camera and responsiveness was defined as maternal talk that commented on the child's actions (e.g., when the child reached for or manipulated an object visible in the head camera). As hypothesized, maternal responsiveness correlated with both mental and non-mental state … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 36 publications
(50 reference statements)
0
8
0
Order By: Relevance
“…Studies focusing on object labeling within JA episodes have also shown that multimodal cues are associated with the child's productive vocabulary development (Akhtar et al, 1991;Dunham et al, 1993). These findings demonstrate the importance of simultaneous multimodal input (e.g., labeling while handling the object) for enhancing a child's word learning and later achievements (Chang & Deák, 2019;Deák et al, 2000;Ruffman et al, 2020).…”
Section: Parent's Referential Cuesmentioning
confidence: 93%
“…Studies focusing on object labeling within JA episodes have also shown that multimodal cues are associated with the child's productive vocabulary development (Akhtar et al, 1991;Dunham et al, 1993). These findings demonstrate the importance of simultaneous multimodal input (e.g., labeling while handling the object) for enhancing a child's word learning and later achievements (Chang & Deák, 2019;Deák et al, 2000;Ruffman et al, 2020).…”
Section: Parent's Referential Cuesmentioning
confidence: 93%
“…More research has been focused on parental MST as related specifically to child MST compared to general child language development. To my knowledge, only three studies have presented data on the latter in children 2 years old or younger (Farkas et al, 2018;Olson & Masur, 2020;Ruffman et al, 2020). Of these, two found concurrent and positive associations between parental MST and child language abilities (Olson & Masur, 2020;Ruffman et al, 2020) whereas one found a concurrent and negative association (Farkas et al, 2018).…”
Section: Relation Between Mental State Talk and Language Developmentmentioning
confidence: 98%
“…To my knowledge, only three studies have presented data on the latter in children 2 years old or younger (Farkas et al, 2018;Olson & Masur, 2020;Ruffman et al, 2020). Of these, two found concurrent and positive associations between parental MST and child language abilities (Olson & Masur, 2020;Ruffman et al, 2020) whereas one found a concurrent and negative association (Farkas et al, 2018). Two of these studies investigated predictive associations and both found that parental MST positively predicted later child language abilities (Farkas et al, 2018;Olson & Masur, 2020).…”
Section: Relation Between Mental State Talk and Language Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Mothers also completed two questionnaires to measure children's receptive and productive vocabulary (see Appendix B) -the MacArthur Communicative Development Inventory (MCDI): Words and Gestures (Fenson et al, 1994) -along with a Mental State Supplement (see Appendix B) used in several previous studies (Ruffman et al, 2018(Ruffman et al, , 2020Taumoepeau & Ruffman, 2006. Parental report has been shown to be a valid measure of child language (e.g., Feldman et al, 2005).…”
Section: Materials and Proceduresmentioning
confidence: 99%